2016
DOI: 10.1038/srep25742
|View full text |Cite
|
Sign up to set email alerts
|

The novel protein DELAYED PALE-GREENING1 is required for early chloroplast biogenesis in Arabidopsis thaliana

Abstract: Chloroplast biogenesis is one of the most important subjects in plant biology. In this study, an Arabidopsis early chloroplast biogenesis mutant with a delayed pale-greening phenotype (dpg1) was isolated from a T-DNA insertion mutant collection. Both cotyledons and true leaves of dpg1 mutants were initially albino but gradually became pale green as the plant matured. Transmission electron microscopic observations revealed that the mutant displayed a delayed proplastid-to-chloroplast transition. Sequence and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Phenotypic analysis showed that the buds and seedling in al4 exhibited an albino phenotype compared to those in RH2B (wildtype, WT) ( Figures 1A–C ). Similar to other chlorotic or albino leaf mutants identified in our laboratory, such as al1 , al2 , and csl1 , the seedlings gradually withered and eventually died ( Zhang et al., 2016 ; Liu et al., 2016b ; Liang et al., 2022 ). The albino phenotype in al4 mutant also could not recover at later developmental stages and eventually died at the three-leaf stage.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Phenotypic analysis showed that the buds and seedling in al4 exhibited an albino phenotype compared to those in RH2B (wildtype, WT) ( Figures 1A–C ). Similar to other chlorotic or albino leaf mutants identified in our laboratory, such as al1 , al2 , and csl1 , the seedlings gradually withered and eventually died ( Zhang et al., 2016 ; Liu et al., 2016b ; Liang et al., 2022 ). The albino phenotype in al4 mutant also could not recover at later developmental stages and eventually died at the three-leaf stage.…”
Section: Resultssupporting
confidence: 73%
“…OsAL1 encodes a sole octotricopeptide repeat protein (OPR) protein, and regulates chloroplast development by coordinating the expression of chloroplast related genes in rice ( Zhang et al., 2016 ). OsAL2 encodes a chloroplast group IIA intron splicing facilitator, and the al2 mutant shows an albino phenotype at the early developmental stage in rice ( Liu et al., 2016b ). OsCSL1 encodes a MAPK kinase kinase22 (MKKK22), and interacts with OsMKK4.…”
Section: Introductionmentioning
confidence: 99%
“…GUN1 ( GENOMES UNCOUPLED 1 ), a central regulator of plastid-to-nucleus retrograde signaling, is a PPR highly expressed in young and expanding leaves of A. thaliana , while in mature leaves, stem, and roots its expression is strongly reduced [ 46 ]. This overexpression in young Arabidopsis seedlings has been described in other chloroplastic PPR genes such as PDM3 and AtDPG1 [ 32 , 47 ]. Therefore, it suggests that the expression of PPRs in plants is conditioned by two factors: the state of cellular differentiation and the state of differentiation of the plastid.…”
Section: Discussionmentioning
confidence: 62%
“…RNA extraction and cDNA synthesis were performed according to the method reported in the previous work [ 53 ]. For real-time quantitative PCR analysis, the reaction was performed using SYBR Green Perfect mix (TaKaRa, Dalian, China) on a CFX96 (Bio-Rad), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%